(Auto)Biographical and cinematographic exposition of Dambudzo Marechera on documentary film and video. (1st April 2013) - Mhiripiri, Nhamo Anthony
Documentary film is a technical artistic method whose importance in the representation of Dambudzo Marechera1 – probably Zimbabwe's best-known creative writer – has not been adequately investigated. Marechera is documented in sequences of The House of Hunger (Chris Austin, 1983), Olley Maruma's After the Hunger and Drought (1985) and in untitled footage shot by Edwina Spicer (1984). These documentaries have cinematographic significance, but they also challenge and reproduce popular impressions of Marechera as an eccentric crazy writer. Besides communicating pro-filmic visuals of Marechera himself, the documentaries offer extensive oral presentations by Marechera on a broad range of topics, including his sanity or insanity and his notions on censorship, identity and his writing habits and plans. This article will outline the structure of each individual documentary, and the relationships between Marechera and the films' directors will be explored.